Study of the morphological features of the peritoneum of white rats and the method of its extraction - Pajdarkina , A.P.; Kushch , O.G. (Морфологія / Morphologia / Morfologìâ, 2023)
Background. Objective data on topographic pictures of internal organs and their structures are important for the development of effective manipulations of surgical interventions. Despite significant achievements in the field of surgery, anesthesiology and resuscitation and the introduction of the latest technologies into medical practice, the results of treatment of patients with acute diseases of the abdominal cavity remain unsatisfactory. Objective. To study the morphological features of the components of the peritoneum, their topography and features of the absorption of film material in normal white rats for further histological studies. Methods. The morphological study of the mesentery of the small intestine included a macroscopic, histological and morphometric study. The area of the mesentery of the small and large intestines was calculated by the planimetric method. Film samples of the mesentery of the small and large intestines, as well as the large cap, were taken from the studied group of rats and carefully transferred to the prepared, disinfected surface of thin foam. Staining was carried out with hematoxylin and eosin by a generally accepted method. The finished painted samples were immersed in a gelatin-glycerol medium with the addition of carbolic acid as a preservative and studied at different magnifications of the microscope. Results. The parietal peritoneum is one of the leaves of the abdominal wall and is a very thin and transparent membrane, through which small capillaries and a thin layer of adipose tissue localized in separate areas of the peritoneal space are clearly visible. Macroscopic examination allows us to characterize it as a set of dense folds of the peritoneum covering the loops of the small and large intestines, separating them from the back wall of the abdominal cavity, and containing blood vessels. The mesentery is a continuous organ with a characteristic fan-like conformation. A mesentery of the small and large intestine can be characterized as a thin, elastic, smooth, almost transparent, moist and shiny formation of the peritoneum of uniform density, in which blood vessels are located closer to the hollow structure of the small and large intestine. Between the two visceral leaves of the peritoneum of the big cap are localized accumulations of adipose tissue, a large number of blood and lymphatic vessels and nerve fibers. Conclusion. The macroscopic and microscopic structure of the peritoneum and its derivatives were studied, and the topography of the peritoneum leaves was comprehensively considered. A method of taking biological material was developed, based on the peculiarities of individual film structures of the abdominal cavity, and means of taking film material for further morphological studies were proposed.